Regenerative therapies for lumbar degenerative disc diseases: a literature review - Sono, Takashi; Shima, Koichiro; Shimizu, Takayoshi; Murata, Koichi; Matsuda, Shuichi; Otsuki, Bungo (Frontiers in Bioengineering and Biotechnology, 2024)
This review aimed to summarize the recent advances and challenges in the field of regenerative therapies for lumbar disc degeneration. The current first-line treatment options for symptomatic lumbar disc degeneration cannot modify the disease process or restore the normal structure, composition, and biomechanical function of the degenerated discs. Cell-based therapies tailored to facilitate intervertebral disc (IVD) regeneration have been developed to restore the IVD extracellular matrix or mitigate inflammatory conditions. Human clinical trials on Mesenchymal Stem Cells (MSCs) have reported promising outcomes exhibited by MSCs in reducing pain and improving function. Nucleus pulposus (NP) cells possess unique regenerative capacities. Biomaterials aimed at NP replacement in IVD regeneration, comprising synthetic and biological materials, aim to restore disc height and segmental stability without compromising the annulus fibrosus. Similarly, composite IVD replacements that combine various biomaterial strategies to mimic the native disc structure, including organized annulus fibrosus and NP components, have shown promise. Furthermore, preclinical studies on regenerative medicine therapies that utilize cells, biomaterials, growth factors, Platelet Rich Plasma (PRP), and biological agents have demonstrated their promise in repairing degenerated lumbar discs. However, these therapies are associated with significant limitations and challenges that hinder their clinical translation. Thus, further studies must be conducted to address these challenges. growth factors, and platelet-rich plasma (PRP). This literature review summarized the recent advances and challenges in the field of regenerative therapies for lumbar disc degeneration.IVDs comprise a central gelatinous nucleus pulposus surrounded by the annulus fibrosus and cartilaginous endplates. The proteoglycan-rich nucleus is capable of absorbing water and resisting compressive load. The collagen fibers constituting the highly organized lamellar annulus fibrosus provide tensile strength (11). The proteoglycan and water content of the discs reduces with aging and injury. In addition, further changes, such as disorganized matrix; loss of collagen organization; ingrowth of nerves and vessels; decreased cell viability; and increased inflammatory cytokine (IL-1β, IL-6, and TNF-α), C-reactive protein levels, and type II collagen levels, have also been reported (12-16) (Figure). These molecular changes result in structural breakdown, reduction in disc height, annular fissuring, radial bulging, altered biomechanics, nerve compression, instability, herniation, and lower back pain.